Role of corporate identity, image and reputation in investors' behavioral decision making: Does emotional attachment matter? - Usman Ahmad Qadri; Mazuri Binti Abd. Ghani; Muhammad Azhar Sheikh (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The aim of this study is to examine the intervening effect of investor emotional attachment between corporate reputation and investors' behavioral decision-making in the context of Pakistan stock exchange (PSX). Specifically, an attempt is made to investigate the indirect effect between corporate identity and investors' behavioral decision making via corporate image, emotional attachment, and corporate reputation. The data collectedfrom 220 individual small equity investors, who maintainedtheir stock accounts throughstockbrokers in PSX. Structural equation modeling was used to test the study hypotheses with help of SPSS.Results confirmed the partial mediation effect of emotional attachment between corporate reputation and investors' behavioral decision-making. In addition, Results supported the indirect effect between corporate identity and investors' behavioral decision making via corporate image, emotional attachment, and investors' behavior. The findings provide fundamental facts to the executives of the firms in Pakistan who want to assess the investor's behavioral decision-making in the equity markets. Further, this study will help to understand the emotional aspects of the individual investors and will enable the policymakersand corporations to understand the decision makingbehaviorof the individual small equity investors and draw their future policies to regulatethe equity markets
Keywords: 330; corporate reputation; corporate image; corporate identity; emotional attachment; investors behavioral decision making; Pakistan stock exchange (PSX)